Lessons learned from understanding chemotherapy resistance in epithelial tubo-ovarian carcinoma from BRCA1and BRCA2mutation carriers. (December 2021) - Le Page, Cécile; Amuzu, Setor; Rahimi, Kurosh; Gotlieb, Walter; Ragoussis, Jiannis; Tonin, Patricia N.
Abstract: BRCA1 and BRCA2 are multi-functional proteins and key factors for maintaining genomic stability through their roles in DNA double strand break repair by homologous recombination, rescuing stalled or damaged DNA replication forks, and regulation of cell cycle DNA damage checkpoints. Impairment of any of these critical roles results in genomic instability, a phenotypic hallmark of many cancers including breast and epithelial ovarian carcinomas (EOC). Damaging, usually loss of function germline and somatic variants in BRCA1 and BRCA2, are important drivers of the development, progression, and management of high-grade serous tubo-ovarian carcinoma (HGSOC). However, mutations in these genes render patients particularly sensitive to platinum-based chemotherapy, and to the more innovative targeted therapies with poly-(ADP-ribose) polymerase inhibitors (PARPis) that are targeted to BRCA1/BRCA2 mutation carriers. Here, we reviewed the literature on the responsiveness of BRCA1/2-associated HGSOC to platinum-based chemotherapy and PARPis, and propose mechanisms underlying the frequent development of resistance to these therapeutic agents.